Immediate Postoperative Pain: An Atypical Presentation of Dropped Gallstones after Laparoscopic Cholecystectomy - Samba Binagi; Jason Keune; Michael Awad (Case Reports in Surgery)
Cholecystectomy is one of the most commonly performed surgical procedures in the United States. A common complication is dropped gallstones, and the diversity of their presentation poses a substantial diagnostic challenge. We report the case of a 58-year-old man presenting with chronic right upper quadrant hours status post cholecystectomy. Imaging demonstrated retained gallstones in the perihepatic space and symptoms remitted following their removal via laparoscopic operation. Gallstones are lost in roughly 1 in 40 cholecystectomies and are usually asymptomatic. The most common presentations are months or years status post cholecystectomy due to fistula, abscess, or sinus tract formation. We report this case hoping to bring light to a rare presentation for dropped gallstones and provide advice on the management of this common complication of cholecystectomy.